USE OF HEPATOPROTECTOR IN COMPLEX TREATMENT OF PATIENTS WITH CHRONIC VIRAL HEPATITIS C - Juraev Bobur Rakhmonovich (Web of Journals Publishing, 2024)
The article presents an analysis of clinical manifestations, laboratory parameters, the nature and frequency of adverse reactions, and the frequency of a positive virological response in 20 patients with chronic viral hepatitis C (HCV) who received combined antiviral therapy with pegintron and ribavirin with the inclusion of a hepatoprotector, 2 tablets 3 times a day, for 3 months compared with a control group of HCV patients who were prescribed similar antiviral therapy without a hepatoprotector. It was found that after treatment in the main group of patients, clinical manifestations of hepatitis were relieved 7-10 days earlier, cytolytic syndrome normalized, a positive virological response increased by 20%, and the frequency of severe adverse reactions of interferon therapy requiring treatment interruption decreased by 10%. A conclusion was made about the advisability of including the hepatoprotector Livomed in the course of antiviral therapy in patients with HCV.
Keywords: Liver damage, clinical manifestations, liver function tests, cirrhosis, hepatoprotector.